Dietary Purple Potato Supplementation Ameliorates Gut Inflammation and Associated Colitis. (7th June 2021) - Bibi, Shima; Xue, Yansong; He, Yang; Du, Min; Chew, Boon; Navarre, Duroy; Zhu, Mei-Jun
Abstract: Objectives: The incidence of inflammatory bowel disease (IBD) is rapidly increasing worldwide. Patients with IBD experience increased susceptibility to colorectal cancer and are associated with morbidity and mortality. Diets are known factors associated with IBD. This study examined the beneficial effects of dietary purple potato against spontaneous colitis and improving gut microbiota in interleukin (IL)-10-deficient mice, a commonly used IBD mice model. Methods: IL-10-deficient mice at 7-week-old were assigned to a standard rodent diet (CON) or a control diet supplemented with 10% purple potato (dry feed weight) for 11 weeks, when colonic tissues were collected for histological and biochemical analyses. Results: Purple potato supplementation had no effect on feed intake and body weight in IL-10-deficient mice during the 11-week feeding trial. Purple potato supplementation improved the colitis symptom and the integrity of the colonic epithelial structure with reduced inflammation and pathological scores. Furthermore, the density of goblet cells and differentiation markers for goblet cells was enhanced due to PP supplementation. Conclusions: Data collectively showed that dietary purple potato supplementation had protective effects against colitis onset in IL-10-deficient mice and improved gut epithelial structure, providing a promising dietary approach for the management and prevention of colitis. Funding Sources: USDA-NIFA and Northwest Potato Research Consortium.